Criteria for the selective use of contrast‐enhanced intra‐operative ultrasound during surgery for colorectal liver metastases. Issue 11 (15th May 2014) - Torzilli, Guido; Botea, Florin; Donadon, Matteo; Cimino, Matteo; Procopio, Fabio; Pedicini, Vittorio; Poretti, Dario; Montorsi, Marco
Abstract: Background: Contrast‐enhanced intra‐operative ultrasound (CE‐IOUS) for colorectal liver metastases (CLMs) has become a part of clinical practice. Whether it should be selectively or routinely applied remains unclear. The aim of this study was to define criteria for the use of CE‐IOUS. Methods: One‐hundred and twenty‐seven patients underwent a hepatectomy for CLMs using IOUS and CE‐IOUS. All patients underwent computed tomography (CT) and/or magnetic resonance imaging (MRI) within 2 weeks prior to surgery. The reference was histology, and imaging at 6 months after surgery. Univariate and multivariate analyses were performed. Statistical significance was set at P = 0.05. Results: Using IOUS an additional 172 lesions in 51 patients were found. CE‐IOUS found 14 additional lesions in 6 patients. Seventy‐eight CLMs in 38 patients appeared within 6 months after surgery. The sensitivity, specificity, positive‐ and negative‐predictive value were 63%, 98%, 100% and 27% for pre‐operative imaging, 87%, 100%, 100% and 52% for IOUS, and 89%, 100%, 100% and 56% for IOUS+CE‐IOUS, respectively. CE‐IOUS allowed better tumour margin definition in 23 patients (18%), thus assisting resection. Analyses indicated that the presence of multiple ( P = 0.014), and isoechoic CLMs ( P = 0.049) were independently correlated with new findings at CE‐IOUS. Conclusions: Compared with IOUS, CE‐IOUS improved detection and resection guidance. These additions are significant and demand its use in cases with multiple and isoechoic CLMs.